Deporte : mecanismo para construir capital social (2017)
"This paper examines to what extent the practice of sports leads to higher levels of social capital. The document provides evidence that sports can enhance social networks based on trust, solidarity and cooperation, values that may be considered particularly important for strengthening social capital in a country like Colombia that is highly affected by conflict. The paper also explores the benefits of sports beyond health issues, which have received little consideration in academia. The research provides evidence applying an extended cooperation theoretical model, based on Cárdenas (2009) and Ostrom (1998). This extended model is empirically tested with data from the urban Colombian Longitudinal Survey of the University of the Andes from 2013 (ELCA)." -- Tomado del Formato de Documento de Grado.